2008
DOI: 10.1016/j.exphem.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plating density and culture time on bone marrow stromal cell characteristics

Abstract: Objective-Bone marrow stromal cells (MSC) are multipotent adult stem cells that have emerged as promising candidates for cell therapy in disorders including cardiac infarction, stroke and spinal cord injury. While harvesting methods used by different laboratories are relatively standard, MSC culturing protocols vary widely. This study is aimed at evaluating the effects of initial plating density and total time in culture on proliferation, cell morphology, and differentiation potential of heterogeneous MSC cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 30 publications
10
139
0
1
Order By: Relevance
“…Although it has been established that MSCs succumb to senescence during extensive in vitro culture, the optimal cell density for growth is unclear. Using rat MSCs, Neuhuber et al found optimal cell growth when plating at 200 cells per cm 2 compared with 20 cells or 2,000 cells per cm 2 [48]. However, other studies suggest even lower plating densities (~1.5-200 cells per cm 2 ) favor proliferation [25,49,50].…”
Section: Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it has been established that MSCs succumb to senescence during extensive in vitro culture, the optimal cell density for growth is unclear. Using rat MSCs, Neuhuber et al found optimal cell growth when plating at 200 cells per cm 2 compared with 20 cells or 2,000 cells per cm 2 [48]. However, other studies suggest even lower plating densities (~1.5-200 cells per cm 2 ) favor proliferation [25,49,50].…”
Section: Proliferationmentioning
confidence: 97%
“…Multilineage potential is universally used by the community as a way to identify an MSC [4] as well as to quantify progenitor potency. Cryopreservation [16], density gradient isolation [52], and seeding density [48] do not yield appreciable effects on MSC multilineage potential. Despite some disparities [14,15], osteogenic potential is the most commonly retained lineage after passage 5 [13, 16-18, 48, 53] ( Table 1).…”
Section: Multilineage Potentialmentioning
confidence: 99%
“…Morphological heterogeneity in MSCs is generally associated with the presence of cells at different differentiation levels and not with the distinct cell culture subtype (Docheva et al, 2008). Besides, large flat MSC is described as mature senescent cell with low mitotic potential (Neuhuber et al, 2008;Fu et al, 2012). Proliferation rate in mesenchymal stem cells is very high and one MSC can proliferate to 2×106 cells in a single passage in rabbits (Lapi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…47 FGF-2, among placental growth factors, is known to have a most powerful effect on MSCs proliferation. 35 Fortunately, this growth factor seems to be in both fetal and maternal circulations during normal pregnancies. 47,48 On the other hand, there might be a correlation between the type of growth factor isoforms in serum and the types of their receptors.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, three major sub-populations were defined: (a) MSCs with a spindle shape cells, (b) large flat cells and (c) triangle cells. [34][35][36][37] A fourth sub-population as mitotic or round cells was also included. To assess effects of different sera on cell morphology, ADSCs were cultured on coverslips.…”
Section: Morphological Classificationsmentioning
confidence: 99%